Structure and Innervation of the Equine Supraspinous and Interspinous Ligaments. (25th January 2017) - Ehrle, A.; Ressel, L.; Ricci, E.; Singer, E. R.
Summary: Pain related to the osseous thoracolumbar spine is common in the equine athlete, with minimal information available regarding soft tissue pathology. The aims of this study were to describe the anatomy of the equine SSL and ISL (supraspinous and interspinous ligaments) in detail and to assess the innervation of the ligaments and their myofascial attachments including the thoracolumbar fascia. Ten equine thoracolumbar spines (T15‐L1) were dissected to define structure and anatomy of the SSL, ISL and adjacent myofascial attachments. Morphological evaluation included histology, electron microscopy and immunohistochemistry (S100 and Substance P) of the SSL, ISL, adjacent fascial attachments, connective tissue and musculature. The anatomical study demonstrated that the SSL and ISL tissues merge with the adjacent myofascia. The ISL has a crossing fibre arrangement consisting of four ligamentous layers with adipose tissue axially. A high proportion of single nerve fibres were detected in the SSL (mean = 2.08 fibres/mm 2 ) and ISL (mean = 0.75 fibres/mm 2 ), with the larger nerves located between the ligamentous and muscular tissue. The oblique crossing arrangement of the fibres of the ISL likely functions to resist distractive and rotational forces, therefore stabilizing the equine thoracolumbar spine. The dense sensory innervation within the SSL and ISL could explain the severe pain experienced by some horses with impinging dorsal spinous processes. Documentation of the nervous supply of the soft tissues associated with the dorsal spinous processes is a key step towards improving our understanding of equine back pain.